2016
DOI: 10.1242/dev.130849
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-catenin signaling mediates human neural crest induction via a pre-neural border intermediate

Abstract: Neural crest (NC) cells arise early in vertebrate development, migrate extensively and contribute to a diverse array of ectodermal and mesenchymal derivatives. Previous models of NC formation suggested derivation from neuralized ectoderm, via meso-ectodermal, or neural-non-neural ectoderm interactions. Recent studies using bird and amphibian embryos suggest an earlier origin of NC, independent of neural and mesodermal tissues. Here, we set out to generate a model in which to decipher signaling and tissue inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
216
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(240 citation statements)
references
References 83 publications
23
216
0
Order By: Relevance
“…We confirmed that NANOG was sustained by GSK3β inhibition at early stage of differentiation via WNT signaling ( Figure 4E). Wnt signaling is also important to regulate neural patterning through forming morphogen gradients with other signal factors (7,(51)(52)(53). Our data then extend the role of NANOG in patterning the regional specified neural precursors at early stage of differentiation.…”
supporting
confidence: 69%
“…We confirmed that NANOG was sustained by GSK3β inhibition at early stage of differentiation via WNT signaling ( Figure 4E). Wnt signaling is also important to regulate neural patterning through forming morphogen gradients with other signal factors (7,(51)(52)(53). Our data then extend the role of NANOG in patterning the regional specified neural precursors at early stage of differentiation.…”
supporting
confidence: 69%
“…Three major signaling pathways, BMP, WNT, and FGF, work combinatorially to drive expression of neural plate border specifier genes [14,1618]. Crosstalk between signaling pathways result in the formation of the neural plate border; for example, Schille and colleagues in frog, found that WNT/PCP receptor, Ror2, upregulates Gdf6 at the neural plate border [19], thus, linking Wnt/PCP signaling to BMP signaling.…”
Section: Induction and Specification Of The Neural Plate Bordermentioning
confidence: 99%
“…8,10 Just recently, analysis of NC induction in hESCs demonstrated that the differentiation of hESCs into NC cells as indicated by expression of NPB genes including pax3 and msx1 takes place independent of the presence of neural precursors or neuroectoderm. 11 The role of the dorsolateral marginal zone…”
Section: Ectodermal Tissue Interactionsmentioning
confidence: 99%
“…19,30,40,41 Likewise, Wnt/b-Catenin signaling is essential for NPB specification in epiblast explants from chick blastulae, where Wnt activity precedes and upregulates bmp4, 17 as well as for expression of NPB genes in hESCs. 11 Steventon and colleagues have analyzed Wnt/ b-Catenin activity in Xenopus embryos using the TOPFlash reporter gene assay. They observed low Wnt/b-Catenin activity at early gastrula stage 10 in the prospective NC, which rises slightly already till late gastrula stage 12 and continuously increases till mid-neurula stage 17.…”
Section: Wnt Signalingmentioning
confidence: 99%
See 1 more Smart Citation